The way to the Western Sea Lewis & Clark acreoss the continent - Lavender, David Siever (Harper & Row New York, 1988)
Critics have called David Lavender a ""master storyteller"" (Library Journal), his prose ""virile, disciplined, yet personal"" (New York Times), and his book ""a balanced, learned, and lively history of an epochal human exploit"" (Choice). Lavender sets the stage with a lucid account of the imperial rivalries between England, Spain, France, and the United States, and their role in Thomas Jefferson''s decision to sponsor an expedition that might strengthen the young country''s claims to lands it had purchased but never seen. Lavender then takes us through the steps that led to the selection of
Title Page; Copyright Page; Dedication; Contents; List of Maps; Acknowledgments; One: Beginner's Luck; Two: Preparing for the Future; Three: Grappling with Logistics; Four: Trial Run; Five: Facing Reality; Six: Smoky Water; Seven: Emphasis on Indians; Eight: Into Winter; Nine: The Grand Plan; Ten: Forty Below-and Far to Go; Eleven: Hazards by Water; Twelve: The Great Portage; Thirteen: The Great Divide; Fourteen: Hunger; Fifteen: Wild Water; Sixteen: The Farthest Reach; Seventeen: Against the Flow; Eighteen: Peace Mission to the Blackfeet; Nineteen: Hurrying Home; Twenty: Endings. Appendix I: Jefferson's Instructions to LewisAppendix II: The Permanent Party; Appendix III: Much Ado About Little-The Case of the Lydia; Notes; Bibliography; Other titles by David Lavender
Includes Bibliography and Index
Keywords: Lewis, Meriwether -- 1774-1809; Clark, William -- 1770-1838.